2019
DOI: 10.1016/j.bbmt.2018.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Busulfan- or Thiotepa-Based Conditioning in Myelofibrosis: A Phase II Multicenter Randomized Study from the GITMO Group

Abstract: We report a randomized study comparing fludarabine in combination with busulfan (FB) or thiotepa (FT), as conditioning regimen for hematopoietic stem cell transplantation (HSCT) in patients with myelofibrosis. The primary study endpoint was progression-free survival (PFS). Sixty patients were enrolled with a median age of 56 years and an intermediate-2 or high-risk score in 65%, according to the Dynamic International Prognostic Staging System (DIPSS). Donors were HLA-identical sibling (n = 25), matched unrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…This topic has been under frequent debate. A previous French experience showed a modest favorable effect of splenectomy on relapse risk; 7 conversely, in a prospective phase‐II EBMT trial investigating FluBu+ATG RIC platform, splenectomy was associated with a >3‐fold increase in relapse incidence, 9 whereas other research groups have demonstrated no effect on relapse risk 6,8,10 . Certain biological and clinical evidence can sustain the hypothesis that splenectomy per se can affect disease recurrence and progression after transplant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This topic has been under frequent debate. A previous French experience showed a modest favorable effect of splenectomy on relapse risk; 7 conversely, in a prospective phase‐II EBMT trial investigating FluBu+ATG RIC platform, splenectomy was associated with a >3‐fold increase in relapse incidence, 9 whereas other research groups have demonstrated no effect on relapse risk 6,8,10 . Certain biological and clinical evidence can sustain the hypothesis that splenectomy per se can affect disease recurrence and progression after transplant.…”
Section: Discussionmentioning
confidence: 94%
“…Previous work has suggested that “huge” splenomegaly may be associated with a higher risk of graft failure, a significant delay in hematopoietic recovery and an increased occurrence of poor graft function 5,6 . However, conflicting results have been reported in terms of both overall survival (OS) and relapse rates 7‐10 . By way of example, Bacigalupo et al documented a lower non‐relapse mortality (NRM) and improved survival in patients undergoing allo‐HCT with spleen diameters <22 cm 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite these observations, it remains uncertain if splenectomy prior to transplantation is associated with improved outcomes. At present, there is some evidence to support pretransplant splenectomy [49][50][51], but postoperative complications, present in around one-half of all patients [52], could lead to delays in HSCT. Therefore, it is accepted that clinical decisions on surgical reduction of spleen size should be made on an individualized basis [19].…”
Section: Pretransplant Evaluation: Prognostic Scores and Consideratiomentioning
confidence: 99%
“…Accordingly, RIC with fludarabine + thiotepa was adopted in the present case. A recent prospective randomized study compared fludarabine in combination with busulfan or thiotepa as conditioning regimen in 60 patients undergoing HSCT for MF, showing comparable clinical outcome in the two arms [51]. However, other available data are somewhat discrepant on the outcomes of patients undergoing fludarabine-melphalan based RIC regimens [54,61].…”
Section: Pretransplant Evaluation: Prognostic Scores and Consideratiomentioning
confidence: 99%
“…Indeed, there are several reports of faster platelet and/or neutrophil count recovery in splenectomized patients. [3][4][5][6][7][8][9][10][11][12][13] The results regarding other post-transplant outcomes are inconsistent; some studies have found longer overall survival after pretransplant splenectomy, 8,13,14 whereas others observed a higher risk of relapse. 15 In the current issue of the American Journal of Hematology, Polverelli et al showed that splenectomy was associated with a lower rate of non-relapse mortality but a higher relapse rate in MF patients, and with a better overall survival in those with a massive splenomegaly.…”
Section: Introductionmentioning
confidence: 99%